The Reformist Role of Physical Education in Social Development a Historical and Philosophical Analysis - Mohamed Ahmed Hassan (Indonesian Journal Publisher, 2025)
This study explores the historical role of physical education as a tool for social reform through a comparative analytical examination of its trajectories across ancient civilizations Islamic systems the European Renaissance and into the modern era shaped by the challenges of globalization. The research shows that physical education has never been merely a motor activity but a multifaceted societal instrument used to instill discipline integrate marginalized groups support national identity and promote mental and social well-being. The study adopts a historical analytical methodology based on a critical review of intellectual philosophical and social sources surrounding the origins and development of physical education. It analyzes how value systems in each era influenced the content of sport and its reformist function. The findings conclude that physical education has always served as a flexible pillar of social reform constantly interacting with systems of power culture and identity. It deserves to be recognized as a core component in educational and social policy rather than being treated as a marginal subject.